Expert writers’ recommendations in economics research articles: implications for the teaching of English for academic purposes - May Siaw-Mei Liu; Lim, Miin Hwa (Penerbit UKM, 2021)
The presentation of economics research results often constitutes the climax of data-driven research articles in the discipline, but how writers make recommendations based on their results remains a fertile area for an in-depth investigation. To date, no research has been conducted to ascertain the extent to which economics researchers incorporate such recommendations, and how they use language resources to perform the communicative functions involved. Our genre-based study employed the Swalesian move-step analytical framework to examine the occurrence of this pivotal rhetorical category, which makes suggestions based on research findings in economics. This largely qualitative analysis was triangulated via interviews with specialist informants in the field. Our results have shown that recommendations, being a quasi-obligatory move that comprises two noteworthy optional steps, are strategically linked with not only research results but also limitations of the research being reported. The expert writers employ a wide spectrum of language resources, particularly adjectives depicting indeterminacy and noun phrases denoting industrial and policy implications, to tacitly accentuate the value of their results. In regard to pedagogical implications, it is suggested that instructors devise exercises requiring novice writers to construct sentences involving suggestion indicators and verb phrases signalling epistemic modality while guiding learners to make recommendations for future research. With respect to recommendations for practical applications, text-completion exercises may be designed to familiarise learners with the use of active clauses containing nominalisations, which are largely intended to minimise self-mentions and increase objectivity while proposing actions to be taken in real-life settings.